Sorption of hexavalent chromium from synthetic waste water using dolochar - H, Panda; S, Sahoo; N, Tiadi; Dash, R R; R, Mohanty C (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The adsorption characteristics of hexavalent chromium on dolochar, a low cost natural adsorbent, were studied in the laboratory. Dolochar was found to be an efficient adsorbent for chromium removal from synthetic waste water. Dolochar which is a solid waste generated by the sponge iron industry, is processed and put to test as an adsorbent for removal of Cr (VI) ions from aqueous solution. In this paper an attempt has been made to investigate the properties (i.e. physical and chemical) so as to reutilize it as absorbent to absorb the pollutants present in water. The adsorption behavior of dolochar using batch shaking has been studied to remove hexavalent chromium from synthetic waste water. The physical properties of dolochar such as specific gravity, void ratio, porosity, density and chemical properties such as chemical composition have been analyzed. Batch adsorption experiment have been conducted by varying adsorbent dose, adsorbate concentration, pH, particle size, time on removal of chromium of these metal ions. It was found that more than 94% of the removal was achieved under optimal condition. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>